Association of body mass index and risk of death from pancreas cancer in Asians: findings from the Asia Cohort Consortium - Lin, Yingsong (2013)
OBJECTIVE: We aimed to examine the association between BMI and the risk of death from pancreas cancer in a pooled analysis of data from the Asia Cohort Consortium. METHODS: The data for this pooled-analysis included 883,529 men and women from 16 cohort studies in Asian countries. Cox proportional-hazards models were used to estimate the hazard ratios (HRs) and 95% confidence intervals (CIs) for pancreas cancer mortality in relation to BMI. Seven predefined BMI categories (<18.5, 18.5–19.9, 20.0–22.4, 22.5–24.9, 25.0–27.4, 27.5–29.9, ≥30) were used in the analysis, with BMI of 22.5–24.9 serving as the reference group. The multivariable analyses were adjusted for known risk factors, including age, smoking, and history of diabetes. RESULTS: We found no statistically significant overall association between each BMI category and risk of death from pancreas cancer in all Asians, and obesity was unrelated to mortality risk in both East Asians and South Asians. Age, smoking, and history of diabetes did not modify the association between BMI and risk of death from pancreas cancer. In planned subgroup analyses among East Asians, an increased risk of death from pancreas cancer among those with a BMI<18.5 was observed for individuals with a history of diabetes; HR = 2.01(95%CI: 1.01–4.00) (p for interaction=0.07). CONCLUSION: The data do not support an association between BMI and risk of death from pancreas cancer in these Asian populations.